Use of extracorporeal membranous oxygenation in the management of refractory trauma-related severe acute respiratory distress syndrome: a national survey of the Eastern Association for the Surgery of Trauma. Issue 1 (12th August 2019) - Raff, Lauren; Kerby, Jeffrey David; Reiff, Donald; Jansen, Jan; Schinnerer, Eric; McGwin, Gerald; Bosarge, Patrick
Abstract : Objective: To report results of a national survey of provider attitudes, observations, and opinions regarding the use of extracorporeal membranous oxygenation (ECMO) to manage severe acute respiratory distress syndrome (ARDS) in trauma patients. Design: A survey was created to query providers on the use of ECMO in trauma, as well as general management principals related to care of the patient with refractory hypoxic respiratory failure. The survey was sent to all members of Eastern Association for the Surgery of Trauma (EAST). Once completed, the survey was returned to the University of Alabama at Birmingham and results were analyzed. Setting/patients: Trauma patients with refractory ARDS. Interventions: None. Measurements and main results: Respondents were from 37 states, the District of Columbia, and Puerto Rico. 56.9% reported institutional ECMO capabilities, but only 45.2% reported using ECMO for trauma patients. Most respondents (90.2%) reported ECMO use in less than or equal to five trauma patients per year. 20.9% think there is not enough data to support its use in trauma but only 4.7% would absolutely not consider ECMO use for trauma patients. Ranking the preferred modality of treatments for refractory ARDS from most to least preferable is as follows: airway pressure release ventilation, bilevel ventilation, paralysis, prone positioning, inhaled nitric oxide, epoprostenol, high-frequency oscillatory ventilation, corticosteroids, surfactant. Conclusions: ARDS has a high mortality among trauma patients. Despite its utility in treating severe ARDS and other pulmonary disease processes, ECMO has not been universally embraced by the trauma community. There are an increasing number of studies that suggest that ECMO is a safe and viable treatment option for trauma patients with ARDS. Based on the results of this survey, ECMO use remains limited by trauma providers that care for patients with refractory hypoxic respiratory failure and ARDS, likely due to a combination of knowledge gaps and lack of access to ECMO. Level of evidence: Level V.